Current distribution of 137cs in sod-podzolic soils of different types of forest conditions - Melnyk, Viktoriia; Kurbet, Tatiana (Eastern-European Journal of Enterprise Technologies, 2018)
We have examined the current distribution of 137Cs in the turf-podzolic forest soils for different types of forest conditions. The analysis of the redistribution of 137Cs in soil in 30 years after the Chernobyl nuclear plant accident is necessary in order to assess the intake of the radionuclide by the various components of forest ecosystems and to substantiate the rehabilitation of forest areas. We have discovered a significant displacement of significant amount of 137Cs to mineral part of the soil in all types of forest conditions under consideration. The maximum magnitudes of the 137Cs specific activity in the forest litter were established, as well as a reduction in this indicator from its upper part (current litter) to the bottom (decomposed). In fresh forests, it reduced by 3.1 times; in fresh subors, by 1.2 times; in wet subors, by 1.5 times. Based on the magnitude of specific activity of 137Cs, the layers of the forest litter for the examined types of forest conditions can be placed in a descending order: decomposed layer > semi-decomposed layer > current litter. The humus-eluvial horizon of the soil with a capacity of 12 cm has concentrated: in fresh forests, 54.0 %; in fresh subors, 40.0 %; in wet subors, 52.8 %, of the total radionuclide activity in the soil, and, together with the content of 137Cs in the forest litter, 75.0 %; 65.8 %, and 71.5 % (according to the type of forest conditions). We have noted a gradual decrease in the137Cs specific activity along the profile to the parent rock. Thus, 26.4 %, 35.7 %, and 28.5 %, respectively, of the total stock of the radionuclide in the soil, have migrated to the lower layers of the soil profile (12–88 cm). The obtained materials have been confirmed by a one-factor dispersion analysis at a 95-% confidence level. Based on the results obtained, one can predict the future levels of radioactive contamination in forestry products